Applying Montessori-based flashcards to teach vocabulary recognition to kindergarten students - Fenny Herlinda Walu Wanja; Rizqi Sabrina; Muhammad Arif; Almas Fildzah Nabilah (University of Muhammadiyah Malang, 2026)
This study aims to explore how kindergarten teachers implement Montessori-based flashcard strategies in teaching English vocabulary recognition. Employing a descriptive qualitative exploratory design, this study was conducted in a private Montessori kindergarten in Kupang, East Nusa Tenggara, Indonesia. Two kindergarten teachers with more than four years of teaching experience participated in the study. Data were collected through semi-structured interviews, classroom documentation, and student learning records, and analyzed using a thematic analysis approach. The findings revealed three major instructional strategies. First, teachers implemented multisensory vocabulary learning by integrating flashcards with the Large Movable Alphabet (LMA), allowing students to associate sounds, letters, and visual images through hands-on activities. Second, teachers applied guided repetition through interactive drilling conducted in short cycles to reinforce vocabulary recognition while maintaining student engagement. Third, teachers used the Three-Period Lesson to support vocabulary consolidation through structured naming, recognition, and recall activities. These findings suggest that Montessori-based flashcard strategies function as flexible instructional practices combining multisensory engagement and structured repetition. The study highlights the importance of teacher responsiveness and offers practical insights for early childhood English teachers.